Comparative genomics of Myxococcus and Pyxidicoccus, including the description of four novel species: Myxococcus guangdongensis sp. nov., Myxococcus qinghaiensis sp. nov., Myxococcus dinghuensis sp. nov., and Pyxidicoccus xibeiensis sp. nov. - Wang, Chunling; Lv, Yingying; Zhou, Lian; Zhang, Yulian; Yao, Qing; Zhu, Honghui (Frontiers in Microbiology, 2022)
Myxobacteria are recognized for fascinating social behaviors and producing diverse extracellular active substances. Isolating novel myxobacteria is of great interest in the exploitation of new antibiotics and extracellular enzymes. Herein, four novel strains were isolated from Dinghu Mountain Biosphere Reserve, Guangdong province and Qinghai virgin forest soils, Qinghai province, China. The phylogenetic analysis based on 16S rRNA gene and genomic sequences indicated that the four strains belong to the genera Myxococcus and Pyxidicoccus, sharing the highly similarities of 16S rRNA gene with the genera Myxococcus and Pyxidicoccus (99.3-99.6%, respectively). The four strains had average nucleotide identity (ANI) values of 82.8-94.5%, digital DNA-DNA hybridization (dDDH) values of 22.2-56.6%, average amino acid identity (AAI) values of 75.8-79.1% and percentage of conserved protein (POCP) values of 66.4-74.9% to members of the genera Myxococcus and Pyxidicoccus. Based on phylogenetic analyses, physiological and biochemical characteristics, and comparative genomic analyses, we propose four novel species of the genera Myxococcus and Pyxidicoccus and further supported the two genera above represented the same genus Description of the four novel species is Myxococcus guangdongensis sp. nov. (K38C18041901T = GDMCC 1.2320T = JCM 39260T), Myxococcus qinghaiensis sp. nov. (QH3KD-4-1T = GDMCC 1.2316T = JCM 39262T), Myxococcus dinghuensis sp. nov. (K15C18031901T = GDMCC 1.2319T = JCM 39259T) and Pyxidicoccus xibeiensis sp. nov. (QH1ED-7-1T = GDMCC 1.2315T = JCM 39261T), respectively. Furthermore, comparative genomics of all 15 species of the genera Myxococcus and Pyxidicoccus revealed extensive genetic diversity. Core genomes enriched more genes associated with housekeeping functional classes while accessory genomes enriched more genes related to environmental interactions, indicating the former is relatively indispensable compared to signaling pathway genes. The 15 species of Myxococcus and Pyxidicoccus also exhibited great gene diversity of carbohydrate-active enzymes (CAZymes) and secondary metabolite biosynthesis gene clusters (BGCs) especially related to glycosyl transferases (GT2 and GT4), glycoside hydrolases (GH13 and GH23), non-ribosomal peptide synthetases (NRPS) and Type I polyketide synthase (PKS)/NRPS hybrids.